Hate crime in the media : a history - Munro, Victoria (Santa Barbara, CA : Praeger, 2014)
"A powerful, uncompromising explanation of how subtle sources of hatred contained throughout our media and culture have resulted in a tolerance for hate crimes in America"--
"See the attached text file"--
Introduction: creating the other -- Making enemies abroad and at home: hate and war -- Unwelcome hordes: immigrants and hate -- The color of hate: race, space, and place -- Sinners, fanatics, and terrorists: the religious other -- Personal space and identity: hate and the Lesbian, Gay, Bisexual, and Transgender community -- The language of hate: hate speech, hate talk, and the First Amendment -- Conclusion: reframing the other.
Includes bibliographical references and index.
Keywords: Hate crimes -- United States; Mass media and culture -- United States